A novel approach with a fuzzy sliding mode proportional integral control algorithm tuned by fuzzy method (FSMPIF) - Nguyen, Tuan Anh (Scientific reports, 2023)
An automobile's vibration can be caused by stimulation from the road's surface. The change in displacement and acceleration values of the sprung mass is used to evaluate the automobile's vibration. Utilizing an active suspension system is recommended in order to attain an increased level of ride comfort. This article presents a novel strategy for regulating the operation of an active suspension system that has been put up for consideration. The PI (Proportional Integral) algorithm, the SMC (Sliding Mode Control) algorithm, and the Fuzzy algorithm served as the basis for developing the FSMPIF algorithm. The signal generated by the SMC algorithm is what is used as the input for the Fuzzy algorithm. In addition, the settings of the PI controller are modified with the help of yet another Fuzzy algorithm. These two Fuzzy methods operate independently from one another and in a setting that is wholly distinct from one another. This algorithm was created in a wholly original and novel way. Using a numerical modelling technique, the vibration of automobiles is investigated with a particular emphasis on two distinct usage situations. In each case, a comparison is made between four different circumstances. Once the FSMPIF method is implemented, the results of the simulation process have demonstrated that the values of displacement and acceleration of the sprung mass are significantly decreased. This was determined by looking at the values before and after implementing the new algorithm. In the first case, these figures do not surpass a difference of 2.55% compared to automobiles that use passive suspension systems. The second case sees these figures falling short of 12.59% in total. As a direct result, the automobile's steadiness and level of comfort have been significantly improved.